Economic impact of preweaning vaccinations on health and performance of weaned feeder cattle - Lynch, J.M.; Houghton, P.L.; Corah, L.R.; Stokka, Gerald L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In October, 1995, 3,565 head of freshly weaned, British-breed calves were received into a weaning facility in southwest Nebraska. Calves were determined to be preconditioned if they had received both viral an d Pasteurella vaccines prior to weaning (PREWEAN; n = 2,315), and all other calves were considered to have no preconditioning (CRTL; n = 1,250). Cattle were processed within 24 hours of arrival, and booster vaccinations were given when appropriate. Average days on feed at the weaning facility were similar between PREWEAN and CTRL calves (52.4 and 50.3 days, respectively), but average daily gain (2.24 vs 1.87 kb) and cost per lb of gain ($.64 vs $.81) were improved (P<.01) for PREWEAN. Processing ($7.48 vs $9.10/hd) and medicine costs ($1.39 vs $5.27/hd) were lower (P<.01) for PREWEAN calves during the weaning phase. Only 10.6% of the PREWEAN calves were treated for sickness, whereas 34.7% of the CTRL calves were treated a t least once (P<.01). Mortality tended to be lower for PREWEAN calves compared to CTRL calves, although it was low for both groups (.26% v s .48%, respectively). The average total cost per head was similar for PREWEAN and CTRL calves ($73.62 vs $72.79, respectively). Theoretical breakevens reflected lower costs and increased performance in PREWEAN cattle . These results suggest that producers should get a return on their money invested in preconditioning programs that include protection against IBR, BVD, PI3, BRSV, and Pasteurella.
Keywords: Beef; Feeder cattle; Weaning; Pre-conditioning; Economics